The ability of hyaluronan fragments to reverse the resistance of C6 rat glioma cell line to temozolomide and carmustine - Karbownik, Michał Seweryn; Pietras, Tadeusz; Szemraj, Janusz; Kowalczyk, Edward; Nowak, Jerzy Zygmunt (Contemporary Oncology/Współczesna Onkologia, 2014)
Aim of the study : Hyaluronan (HA) is an extracellular matrix (ECM) polymer that may contribute to the emergence of anti-cancer drug resistance. Attempts to reverse drug resistance using small hyaluronan oligomers (oHA) are being made. The initial reports suggest that the oHA fraction may effectively reverse anti-cancer drug resistance in glioma models. However, the reversal effects of oHA of defined molecular length on glioma cells have not been investigated yet. In this study, we examined HA fragments containing 2 disaccharide units (oHA-2), 5 disaccharide units (oHA-5), and 68 kDa hyaluronan polymer (HA-68k) as agents possibly reversing the resistance of a C6 rat glioma cell line to temozolomide (TMZ) and carmustine (BCNU). Material and methods: A 3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyl-2H-tetrazolium bromide (MTT) viability assay was used to assess the cytotoxicity of TMZ and BCNU in the presence or absence of the hyaluronan fragments. By comparing viability of the cells, the reversal effects of HA fragments on TMZ and BCNU resistance in C6 glioma cells were assessed. Results : We found statistically significant decreases in the viability of cells in the presence of TMZ+oHA-5 as compared to TMZ alone (51.2 ±4.5 vs. 74.2 ±5.8, p = 0.0031), BCNU+o-HA5 as compared to BCNU alone (49.3 ±4.4 vs. 65.6 ±5.7, p = 0.0119), and BCNU+HA-68k as compared to BCNU alone (55.2 ±2.3 vs. 65.6 ±5.7, p = 0.0496). Conclusions : Hyaluronan oligomers of 5 disaccharide units (oHA-5) significantly reversed the resistance of C6 cells to TMZ and BCNU. The results are only preliminary and a more thorough follow-up investigation is required to assess their actual role.